Efektivitas Program SIPEDULI Sebagai Sistem Pelayanan Administrasi Kependudukan Online di Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Jembrana - Nizla Maulidia; Ni Wayan Supriliyan; Kadek Wiwin Dwi Wismayanti (IJESPG (International Journal of Engineering, Economic, Social Politic and Government), 2023)
The Online Population Administration Program System (SIPEDULI) is one of the efforts of the Regional Government to develop services, namely the Management Information System created by Dukcapil, Jembrana Regency. The purpose of this study was to determine the effectiveness of the SIPEDULI Program service at the Jembrana Regency Population and Civil Registry Service. This study used a descriptive qualitative method with data collection techniques in the form of observation, interviews and documentation. Based on the results of the research analyzed using effectiveness theory, it shows that the effectiveness of the SIPEDULI program has been running but not yet fully because there are still some indicators that are less effective, namely indicators of accuracy. The targets include the unavailability of supporting infrastructure and the unavailability of human resources, as well as socialization indicators that are not yet optimal so that many people still do not know about the existence of SIPEDULI, as well as indicators of the main objective of the program in providing effective services. and efficient service facilities have not been fully realized, while program monitoring indicators have been declared effective because so far this has been done by accommodating public complaints and continuing to evaluate so that the SIPEDULI program will be better in the future. The author provides recommendations in this study, namely holding human resource training, improving facilities and infrastructure to support implementation, holding sustainable outreach.